Diagrammatic scale for evaluation of powdery mildew in eucalyptus - Ruiz, Anny Mery Marcon [UNESP]; de Pieri, Cristiane [UNESP]; Pieroni, Lisandro de Proença [UNESP]; Porcena, Alex Sander; Albuquerque, Fábio Suzart; Furtado, Edson Luiz [UNESP] (Universidade Federal de Santa Maria, 2021)
The Eucalyptus powdery mildew caused by Podosphaera pannosa can cause losses in eucalyptus nurseries in Brazil. The evaluation of this disease and the damages that could be caused by it, as well as the investigation for the efficient controlling forms, lead us to the need of having a visual scale, as means to quantify the severity of this pathosystem. This study had, as its goals, the development of a diagrammatic scale to evaluate the powdery mildew severity in eucalyptus leaves in a nursery home. To do so, symptomatic eucalyptus leaves were collected, scanned, and digitalized to determine the total leaf area and the area occupied with symptoms. Thus, we were able to obtain eight levels of severity based on the sample distribution. To validate the scale, the disease severity had been estimated by ten evaluators, which did not have the scale in hands, and in the sequence, the disease severity was estimated by using the proposed scale in 60 eucalyptus leaves, which had heterogeneous levels of severity. The precision of the obtained estimates obtained was by calculating the coefficient of determination (R²) and a simple linear regression analysis was performed. Precision was found in the visual estimates of the severity of powdery mildew in eucalyptus using the proposed diagrammatic scale, therefore, its use is adequate and being this possible to be used for epidemiological researches and to evaluate control and management strategies.
Escala diagramática para avaliação da severidade de oídio em eucalipto
Keywords: Disease evaluation; Eucalyptus sp; Podosphaera pannosa; Severity scale